2008
DOI: 10.1111/j.1743-6109.2008.00840.x
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Risk Factors of Female Sexual Dysfunction in Young Korean Women: An Internet-Based Survey

Abstract: Introduction In Korea, although male sexual problems have been relatively well addressed, few surveys have been conducted on female sexual dysfunction (FSD) in the general population. In the present study, we investigated the prevalence and identified the risk factors of sexual dysfunction in young Korean women. Aim To evaluate the prevalence and to identify the risk factors of FSD in young Korean women. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
103
10
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(133 citation statements)
references
References 22 publications
(42 reference statements)
13
103
10
7
Order By: Relevance
“…La homosexualidad se encontró asociada positivamente a desarrollar algún tipo de disfunción sexual, como lo demuestra Song y cols (17). Sin embargo, en la revisión no se encontró estudios que evaluaran esta situación, por lo cual es necesario, la investigación y el análisis de disfunción sexual femenina en mujeres homosexuales.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…La homosexualidad se encontró asociada positivamente a desarrollar algún tipo de disfunción sexual, como lo demuestra Song y cols (17). Sin embargo, en la revisión no se encontró estudios que evaluaran esta situación, por lo cual es necesario, la investigación y el análisis de disfunción sexual femenina en mujeres homosexuales.…”
Section: Discussionunclassified
“…Factores de riesgo de disfunción sexual: En los estudios incluidos en esta revisión, cada uno evaluó diferentes factores de riesgo, los más frecuentes fueron: la baja frecuencia de relaciones sexuales, este demostró ser un factor de riesgo significativo en varios de los estudios incluidos (16,17); con un OR 10,67 (IC95% 3,58-31,74) (Tabla IV) en el estudio de Ishak y cols (18); pero en el estudio de Grewal y cols (14), no se encontró asociación entre éste y la presencia de disfunción sexual femenina OR 6,74 (IC95% 0,66-68,54).…”
Section: Tabla II Descripción Y Criterios De Calidad De Los Estudios unclassified
See 1 more Smart Citation
“…It further showed a high rate of hesitancy in seeking help because of economic and sociocultural considerations [2]. Numerous studies from diverse geographic and sociocultural backgrounds have suggested similar problems globally [1, 3, 4, 5, 6, 7, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…FSFI was developed and meticulously validated in the year 2000 [8, 9], which was cross‐validated again in women with mixed sexual disorders [17]. This questionnaire has been successfully translated and psychometrically validated in other languages, including Chinese, Arabic, Persian, Malay, Turkish, Korean, and Japanese [18, 19, 20, 21, 22, 23].…”
Section: Introductionmentioning
confidence: 99%